The transformative pre-Roman Iron Age of the North : The example of the Mang de Bargen cemetery - Schaefer-Di Maida, Stefanie (Danish Journal of Archaeology, 2025)
This paper presents the transformative pre-Roman Iron Age part of the cemetery of Mang de Bargen. So far, the main focus of investigations at this site has been on the Bronze Age, although very intensive activity can also be proven for the pre-Roman Iron Age, which is not only limited to the cemetery, but is also evident in the surroundings. With the Iron Age, changes and innovations in particular in material culture become apparent, which is examined with the present study, especially with regard to relative and absolute dating. Phases within the pre-Roman Iron Age can be delineated. Various features of the cemetery show not only a new institutionalised behaviour in the cremation of the dead, but also a new behaviour in the collecting of the burnt bones at the pyre and their placement in the urn. Furthermore, some urn burials are enclosed with different types of ditches, which can be placed in a supra-regional context. With the addition of environmental data from pollen profiles and find distribution patterns as well as slag pits, the cemetery can be embedded in a region that experiences a transformation with the pre-Roman Iron Age, showing a strong increase in activity in the region.